Football lessons for universities or how to go beyond ranking - Hazelkorn, Ellen; Mihut, Georgiana (Edward Elgar Publishing, 2021)
This is a definition of Football lessons for universities or how to go beyond ranking in the Research Handbook on University Rankings. Gathering unique and thoughtful contributions from leading international scholars, this timely Research Handbook offers diverse perspectives on university rankings twenty years after the first global rankings emerged. It presents an in-depth analysis that reflects the current state of research on rankings, their influence and impact.